Metal-Organic Framework (MOF)-Based Biomaterials for Tissue Engineering and Regenerative Medicine - Shyngys, Moldir; Ren, Jia; Liang, Xiaoqi; Miao, Jiechen; Blocki, Anna; Beyer, Sebastian (Frontiers in Bioengineering and Biotechnology, 2021)
The synthesis of (Metal-organic Frameworks) MOFs and their evaluation for various applications is one of the largest research areas within materials sciences and chemistry. Here, the use of MOFs in biomaterials and implants is summarized. Focus is given on MOFs as bioactive component to aid tissue engineering and to augment clinically established or future therapies in Regenerative Medicine. A summary of synthesis methods suitable for TERM laboratories and key properties of MOFs relevant to biomaterials is provided. The use of MOFs is categorized according to their targeted organ (bone, cardio-vascular, skin and nervous tissue) and whether the MOFs are used as intrinsically bioactive material or as drug delivery vehicle. Further distinction between in-vitro and in-vivo studies provides a clear assessment on the current progress of MOF based biomaterials. The limited number of publications in this emerging research direction allows a nearly comprehensive overview at present. While a number of excellent studies have been published, future studies will need to clearly highlight the safety and added value of MOFs compared to established materials for clinical TERM applications. The scope of the present review is clearly delimited from the general ‘biomedical application’ of MOFs that focuses mainly on drug delivery or diagnostic applications not involving aspects of tissue healing or better implant integration.